2023
DOI: 10.1039/d3dt02555a
|View full text |Cite
|
Sign up to set email alerts
|

Compositionally engineered Cd–Mo–Se alloyed QDs toward photocatalytic H2O2 production and Cr(vi) reduction with a detailed mechanism and influencing parameters

Jyotirmayee Sahu,
Sriram Mansingh,
Bhagyashree Priyadarshini Mishra
et al.

Abstract: Photocatalytic H2O2 production and Cr(vi) reduction using Cd–Mo–Se alloyed QDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The O 2 reduction reaction (ORR) was carried out by dispersing 40 mg of photocatalyst in 50 mL of solution containing 10 vol % isopropanol as a sacrificial agent as well as a proton source. The amount of H 2 O 2 produced was determined by using a literature-reported spectroscopic method . The detailed experimental procedure of the photocatalytic study is elaborately explained in the Supporting Information file.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The O 2 reduction reaction (ORR) was carried out by dispersing 40 mg of photocatalyst in 50 mL of solution containing 10 vol % isopropanol as a sacrificial agent as well as a proton source. The amount of H 2 O 2 produced was determined by using a literature-reported spectroscopic method . The detailed experimental procedure of the photocatalytic study is elaborately explained in the Supporting Information file.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of H 2 O 2 produced was determined by using a literature-reported spectroscopic method. 13 The detailed experimental procedure of the photocatalytic study is elaborately explained in the Supporting Information file. 244), (604̅ ), (62̅ 4̅ ) and (800) crystallographic planes of roxbyite Cu 58 S 32 phase with triclinic crystal system (PDF# 00-064-0278) (Figure 1a).…”
Section: Photocatalytic Activity Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Patnaik et al has designed a Au-Pd-g-C 3 N 4 composite for Cr(VI) reduction and found that the fabricated material achieved 56% of Cr(VI) reduction under visible light irradiation for 2 h. 12 Similarly, Sahu et al synthesized Cd-Mo-Se alloyed quantum dots for Cr(VI) reduction, which displayed 93.6% reduction in 2 h of irradiation. 13 Das and his team members fabricated ZnFe 2 O 4 -Al 2 O 3 -MCM-41 by a wet-impregnation method for photocatalytic Cr(VI) reduction and exhibited 66% reduction in 60 minutes of sunlight irradiation. 14 Encouragingly, semiconductor-based photocatalysis is the most promising and sustainable technology developed so far, which has the ability to solve all these problems.…”
Section: Introductionmentioning
confidence: 99%